ASSESSING THE OUTCOME OF 90% TRICHLOROACETIC ACID BY CHEMICAL RECONSTRUCTION OF SKIN SCARS TECHNIQUE IN THE PATIENTS WITH ICE PICK ACNE SCARS (Asian Journal of Medical Research and Health Sciences (A-JMRHS), 2025)
applied locally on the acne scars to ultimately attain collagenization by initiating the process of inflammation. This in turn can reduce the appearance of scars which is the desired cosmetic result for the patient. Material and Methods: 20 patients with predominantly atrophic ice pick post acne scars were treated with chemical reconstruction of skin scars technique, using 90% trichloroacetic acid, which was applied with a wooden toothpick, at 2 weekly settings for four sittings. The outcome was assessed on the basis of clinical assessment, Goodman and Baron Scale, patient’s feedback after the fourth treatment of treatment; clinical photographs at each sitting and at the three months follow up after the last treatment. Results: About 70% improvement was seen in 16 out of 20 patients and around 50% improvement was observed in the remaining 4 patients. No cosmetic disfigurement or significant side effects were noted. 3 months after the last treatment 2 patients noted a decrease in improvement. Conclusion: Chemical reconstruction of skin scars technique, using 90% trichloroacetic acid, is an effective modality for management of ice pick acne scars.
Keywords: Acne scars; Ice pick scars; Trichloroacetic acid; Chemical reconstruction